The application of headspace solid-phase microextraction as a preparation approach for gas chromatography with mass spectrometry - Jerković, Igor (Array, 2020)
Reviewed in brief are the selected results of the application of headspace solid-phase microextraction as a preparative approach for gas chromatography – mass spectrometry (HS-SPME/GC-MS) for natural organic compounds research at the University of Split, Faculty of Chemistry and Technology. A wide variety of headspace compounds from different natural sources has been identified: lower aliphatic compounds (e.g., C5- and C6-compounds), aromatic compounds, monoterpenes (e.g., linalool derivatives (oxides, anhydro-oxides, epoxides), hotrienol), sesquiterpenes (e.g., eudesmol isomers, hydrocarbons), and C9- and C13-norisoprenoids (e.g., 3,4-dihydro-3-oxoedulan, 4-oxoisophorone, trans-β-damascenone). These compounds are important phytochemicals as flavour/fragrance compounds, chemical markers of the botanical origin or others (e.g., allelochemicals, pheromones, or acaricide residue).